Impact of intra-fractional motion on dose distributions in lung IMRT. Issue 1 (9th March 2021) - Chetvertkov, Mikhail A.; Vassiliev, Oleg N.; Yang, Jinzhong; Wang, He C.; Liu, Amy Y.; Liao, Zhongxing; Mohan, Radhe
Abstract: Aim: To investigate the impact of intra-fractional motion on dose distribution in patients treated with intensity-modulated radiotherapy (IMRT) for lung cancer. Materials and methods: Twenty patients who had undergone IMRT for non-small cell lung cancer were selected for this retrospective study. For each patient, a four-dimensional computed tomography (CT) image set was acquired and clinical treatment plans were developed using the average CT. Dose distributions were then recalculated for each of the 10 phases of respiratory cycle and combined using deformable image registration to produce cumulative dose distributions that were compared with the clinical treatment plans. Results: Intra-fractional motion reduced planning target volume (PTV) coverage in all patients. The median reduction of PTV covered by the prescription isodose was 3·4%; D98 was reduced by 3·1 Gy. Changes in the mean lung dose were within ±0·7 Gy. V20 for the lung increased in most patients; the median increase was 1·6%. The dose to the spinal cord was unaffected by intra-fractional motion. The dose to the heart was slightly reduced in most patients. The median reduction in the mean heart dose was 0·22 Gy, and V30 was reduced by 2·5%. The maximum dose to the oesophagus was also reduced in most patients, by 0·74 Gy, whereas V50 did not change significantly. The median number of points in which dose differences exceeded 3%/3 mm was 6·2%. Findings: Intra-fractional anatomical changes reduce PTV coverage compared to the coverage predicted by clinical treatment planning systems that use the average CT for dose calculation. Doses to organs at risk were mostly over-predicted.